Prospects and Challenges of Rural Small Scale Industries in the Sunyani Municipality of Ghana - Addaney, Michael; Akudugu, Jonas Ayaribilla; Asare, Edwin Supreme (Asian Development Policy Review, 2016)
Rural Small Scale Industries (RSSIs) contribute significantly to economic development. Despite their prospects, RSSIs in Ghana face many challenges that need timely planned interventions to propel them on the path of sustainable growth and development. This article is based on a study conducted in 2016 on the prospects and challenges of RSSIs in Ghana. Through a case study approach, both primary and secondary data were gathered to examine the prospects and challenges facing a sampled 200 RSSIs in the Sunyani Municipality of Ghana. Most of the RSSIs studied were in their first five years of operation. The research revealed that the three main challenges of promoting RSSIs are poor management skill, limited access to credit, and inadequate market. Another revelation of the research was that RSSIs which received training in capacity building and advisory services improved in their business operations and activities. And, this led to better output. The contrary was however the case for those RSSIs which were not provided with such capacity building and business advisory services. The study thus recommends timely provision of improved capacity building services, easy access to open and integrated market as well as to low-interest rate credits with flexible terms of payment to RSSIs to propel their sustainable growth.